ANALISIS PENDAPATAN KELUARGA PETANI TEBU DI KABUPATEN PEKALONGAN (INCOME ANALYSIS ON SUGARCANE FARMER HOUSEHOLDS IN PEKALONGAN) - Sumastuti, Efriyani (Jurnal Ilmu-Ilmu Pertanian, 2009)
The objectives of this study are (l) to analyze farm household income; (2) to determine factors affecting farm household income in sugarcane area. A cross-section farm survey was conducted in the sugarcane area of Pekalongan District. Two sample sub-districts were selected in this study, one sub-district representing an area having high sugarcane productivity, and the other an area with low productivity. Two sample villages were selected from each sample sub-district, one tillage is nearby the sub-district town, while the other is relatively far Twenty five farm households having lowland allocated for sugarcane farming were randomly chosen as samples from sample village. Regression analysis was applied to estimate farm household income determination function. The results of this study show that the household income for the non-farm employment, sugarcane fanning and the non-sugarcane were Rfi.ai\.so|; Rp1.673.265 and Rp1.476.717. The regression analysis indicates that the total farm household income was positively determined by the sugarcane farm size, dry-land hectarage, family lab or force and wage rate of the non-farm employrnent.